Bangladesh : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
Executive Directors commend Bangladesh in addressing the major challenges to growth and poverty reduction. The strategy is comprehensive and confronts the key issues impeding sustainable development and inclusive growth in Bangladesh. Implementing sound macro-financial policies, intensifying revenue mobilization, improving the business environment, ensuring trade liberalization, and improving governance and accountability are top priorities. Actions should be sequenced according to these priorities. Severe external shocks could reignite macroeconomic pressures and undermine socioeconomic targets.